DESIGN OF VERTICAL AXIS SAVONIUS WINDMILL FOR GENERATING ELECTRICITY USING PERMANENT MAGNET - Rochman, Sagita (UNIPA PRESS, 2020)
At present the use of wind energy in Indonesia is still relatively low, but has enormous potential. One reason is because the average wind speed in the territory of Indonesia is classified as low wind speed, which ranges from 3 m / s to 5 m / s making it difficult to produce electrical energy on a large scale. However, the wind potential in Indonesia is available almost all year long, making it possible to develop small-scale power generation systems. Innovations in modifying windmills need to be developed so that in conditions of low wind speeds can produce electrical energy. In this research, a prototype was developed by designing a vertical axis windmill power plant model Savonius using a permanent magnet generator, which can produce optimal electrical energy by utilizing relatively low wind speeds.From the generator test it was found that with a rotor rotation of 50 rpm up to 500 rpm can produce an electrical voltage of 0.02V to 10V and an electric current of 0.60A to 4.53A.